2014
DOI: 10.1108/lhs-09-2012-0029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical leadership style and hand hygiene compliance

Abstract: Purpose – The purpose of this paper is to investigate to what extent an engaging or authentic leadership style is related to higher levels of patient safety performance. Design/methodology/approach – A survey and/or interview of 53 medical and dental staff on their perceptions of leadership style in their unit was conducted. Scores obtained from 51 responses were averaged for each question and overall performance was compared with unit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The survey results show that food handlers have a poor perception of their leaders' management of food-hygiene practices. It is similar to that found by Stevens et al (2014) and Sharma (2012), where leadership also has a negative impact on hygiene practices and even suggested that factors such as the environment, education, role modeling, and knowledge may be more important determinants. Leaders may not necessarily be professional practitioners, but can still be considered role models because of other management qualities or personality traits.…”
Section: Discussion and Implications Of The Studysupporting
confidence: 71%
“…The survey results show that food handlers have a poor perception of their leaders' management of food-hygiene practices. It is similar to that found by Stevens et al (2014) and Sharma (2012), where leadership also has a negative impact on hygiene practices and even suggested that factors such as the environment, education, role modeling, and knowledge may be more important determinants. Leaders may not necessarily be professional practitioners, but can still be considered role models because of other management qualities or personality traits.…”
Section: Discussion and Implications Of The Studysupporting
confidence: 71%
“…It shows that professionals too can lack knowledge and awareness of correct hand-hygiene practices. Consistently, Stevens, Hemmings, Scott, Lawler, and White (2014) found a negative relationship between leadership style and hand hygiene compliance when they interviewed 53 medical and dental staff to unravel clinical leadership style and hand hygiene compliance. In this sense, leadership role modeling is effective in improving patient safety performance through increasing hand hygiene compliance.…”
Section: Leadership Effectiveness (Le) and Food-hygiene Practicesmentioning
confidence: 83%
“…Firstly, food handlers have a poor perception of their leaders' management of food-hygiene practices, which Stevens et al (2014) and Sharma (2012) also found. This negative outcome suggests that other factors like environment, education, role modeling, and knowledge may be more important determinants.…”
Section: Discussion and Implications Of The Studymentioning
confidence: 99%
“…Safety leadership has been widely admitted to be critical, specifically when it comes to instilling a safe work culture [59,60]. Leaders have already been actively involved in safety and have been studied by previous scholars in various contexts [61][62][63][64][65][66][67]. These researchers applied leadership theories or models to establish variables in order to measure leadership in the context of workplace safety and health.…”
Section: Safety Leadershipmentioning
confidence: 99%